Distilling the influence of alcohol : aguardiente in Guatemalan history - Carey, David, Jr., 1967-; Taylor, William B. (University Press of Florida, 2012)
Sugar, coffee, corn, and chocolate have long dominated the study of Central American commerce, and researchers tend to overlook one other equally significant commodity: alcohol. Often illicitly produced and consumed, aguardiente (distilled sugar cane spirits or rum) was central to Guatemalan daily life, though scholars have often neglected its fundamental role in the country's development. Throughout world history, alcohol has helped build family livelihoods, boost local economies, and forge nations. The alcohol economy also helped shape Guatemala's turbulent categories of ethnicity, race, c.